Learner English : a teacher's guide to interference and other problems - Smith, Bernard, 1937-; Swan, Michael (New York : Cambridge University Press, 2001)
Presents a comprehensive guide for ESL teachers to help them gain a better understanding of their students' primary language and the various problems they may encounter learning English.
Professional
Keywords: English language -- Study and teaching -- Foreign speakers; Interference (Linguistics); English as a second language; English language -- Study and teaching; Linguistics